UNVEILING ECOLOGICAL DYNAMICS AND PATTERNS IN AN URBAN-TO-RURAL GRADIENT OF FOREST FRAGMENTS IN THE ATLANTIC FOREST BIOME - Jessica Thalheimer de Aguiar; Tarik Cuchi; Rogério Bobrowski (Revista Árvore)
ABSTRACT The floristic composition and forest structure have been extensively documented as a wellestablished basis for ecological studies. However, distinctions along the urban-to-rural gradient are limited for neotropical ecosystems. Therefore, we analyzed the floristic, diversity, and spatial distribution patterns of tree species along an urban-to-rural gradient of forest fragments in the Atlantic Forest Biome. Thus, a 1.0 ha area was sampled in each fragment (urban, peri-urban, and rural) based on 50 unit samples of 20.0 x 10.0 m. Data on species, diameter at breast height (DBH), total height, and position (x and y coordinates) were collected. Analyses were conducted on the secondary succession stage, phytosociology, data distribution, floristic similarity, diversity indices, and spatial distribution (total and main species). A significant floristic difference was found among the fragments along the urban-torural gradient (p<0.01), with the rural forest in a late-successional regeneration stage and the others in an intermediate stage. Urban and rural forests differed significantly in diversity (p<0.01). The urban fragment exhibited an aggregated species distribution up to 50.0 m, while the peri-urban fragment showed up to 30.0 m aggregation. Spatial distribution in the rural fragment was completely random. However, the distribution pattern of a considered species varies depending on the fragment type. We identified differences among the three forest fragments (floristics, diversity, and spatial distribution of species) due to the influence of the urban ecosystem. The procedures adapted to assess the secondary forest succession stage were found to be reliable to mitigate the subjectivity in Conama Resolution 02/1994.